2014
DOI: 10.1038/ncomms4150
|View full text |Cite|
|
Sign up to set email alerts
|

The miR-363-GATA6-Lgr5 pathway is critical for colorectal tumourigenesis

Abstract: Aberrant activation of Wnt signalling results in colorectal tumours. Lgr5 is specifically expressed in stem cells of the intestine and has an essential role in maintaining tissue homeostasis. Lgr5-positive stem cells are responsible for the intestinal adenoma initiated by mutations in adenomatous polyposis coli. Furthermore, Lgr5 interacts with R-spondins and thereby activates Wnt signalling. However, the function of Lgr5 in colorectal tumourigenesis is unclear. Here we show that LGR5 is required for the tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 48 publications
4
86
0
Order By: Relevance
“…8D) may be specific to HT-29 cells or could occur in other cell types. We immunoblotted various cell lines with the phospho-Ser 37 antibody in comparison to affinity-purified antisera binding the nonphosphorylated peptide surrounding Ser 37 (see Materials and Methods) and to other commercial GATA6 antibodies (100, 118). In HCT-8 and DLD-1 colorectal cancer lines, AC16 cardiomyocytes (110), and MCF10A-5E breast epithelial cells (119), we observed the 60 and 75-kD forms of GATA6 L , which were phosphorylated to variable extents according to phospho-Ser 37 immunoreactivity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8D) may be specific to HT-29 cells or could occur in other cell types. We immunoblotted various cell lines with the phospho-Ser 37 antibody in comparison to affinity-purified antisera binding the nonphosphorylated peptide surrounding Ser 37 (see Materials and Methods) and to other commercial GATA6 antibodies (100, 118). In HCT-8 and DLD-1 colorectal cancer lines, AC16 cardiomyocytes (110), and MCF10A-5E breast epithelial cells (119), we observed the 60 and 75-kD forms of GATA6 L , which were phosphorylated to variable extents according to phospho-Ser 37 immunoreactivity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our data also imply that LGR5 is dispensable for tumour growth in these conditions, in contrast to recent reports using CRC cell lines knocked down for Gata6 (ref. 20). Gene set enrichment analysis also indicated a prominent enrichment in components of the transforming growth factor TGF-β superfamily, most of which belong to the BMP signalling pathway (Supplementary Table 3).…”
Section: Gata6mentioning
confidence: 95%
“…1b). Indeed, GATA6 has been very recently identified as a direct regulator of LGR5 expression in CRC cells 20 . We corroborated these findings through experiments of shRNA-mediated knockdown, overexpression and chromatin immunoprecipitation (ChIP) of GATA6 in CRC cells ( Fig.…”
Section: Screening For Genes That Regulate Stemness In Crcmentioning
confidence: 99%
“…Furthermore, there are other conflicting reports regarding the functional role of LGR5 in colon cancer tumorigenesis. Some studies reported that RSPO/LGR5 signaling has a tumor suppressive activity in colon cancer (8;13) whereas others showed that LGR5 promotes tumorigenicity (14). Therefore, the role of LGR5 in colon cancer tumorigenesis remains ambiguous, although in a transposon mutagenesis study RSPO2 scored second only to APC as a colon cancer tumor suppressor locus (15).…”
Section: Introductionmentioning
confidence: 99%